Anti-Apoptotic Gene Delivery with cyclo-(d-Trp-Tyr) Peptide Nanotube via Eye Drop Following Corneal Epithelial Debridement - Yu-Hsing Lee; Shwu-Fen Chang; Jiahorng Liaw (MDPI AG, 2015)
Corneal keratocyte apoptosis triggered by cornel debridement is one mechanism of corneal disorders. In this study, the feasibility of cyclo-(d-Trp-Tyr) peptide nanotubes (PNTs) as carriers of caspase 3 silence shRNA delivery was assessed. A model of epithelial injury by epithelial debridement was applied to investigate the feasibility of PNTs as gene delivery carriers on corneal injury. First, the PNTs were found within 2 μm in length and 300 nm in width by an atomic force microscope and confocal laser microscope system. Plasmid DNAs were observed to be associated with PNTs by atomic force microscope and confocal laser scanning microscope. The plasmids were associated with tyrosine of PNTs with a binding constant of 2.7 × 108 M−1. The stability of plasmid DNA with PNTs against the DNase was found at 60 min. Using thioflavin T pre-stained PNTs on the corneal eye drop delivery, the distribution of PNTs was in the epithelial and stroma regions. After corneal debridement, the rhodamine-labeled plasmid DNA and thioflavin T pre-stained PNTs were also delivered and could be observed in the stroma of cornea. PNTs complexed with anti-apoptotic plasmid caspase 3 silencing shRNA eye drop delivery decreased 41% of caspase 3 activity after the first dose by caspase 3 activity and Western blot analysis.